In vitro Pharmaceutical Equivalence Study of Three Brands of Atenolol Tablets Available in Bangladesh - Begum, Rehana; Sultan, Md Zakir; Chowdhury, Jakir Ahmed; Amran, Md Shah (Dhaka University Journal of Pharmaceutical Sciences, 2019)
The aim of the present work was to assess the pharmaceutical equivalence of three brands of atenolol (50 mg) tablets available in Bangladesh using in vitro dissolution study. The dissolution study was carried out using the paddle apparatus according to the guidelines of United States Pharmacopoeia (USP). The dissolution profiles of three locally manufactured atenolol tablets were determined and compared with the dissolution profile of atenolol tablet from innovator’s company. All samples attained more than 85% dissolution within 10 minutes. Mean dissolution values were employed to estimate difference factor (f1) and similarity factor (f2). Difference factor (f1) and similarity factor (f2) were used to assess in vitro bio-equivalency among the three brands. Other general quality assessment parameters such as hardness, friability and disintegration time were also determined. All brands complied with the official specifications for hardness, friability and disintegration time. The study indicated that all brands can be prescribed interchangeably. Dhaka Univ. J. Pharm. Sci. 18(1): 43-48, 2019 (June)